Morphological conservatism in Enggano subordinate clauses - Zobel, E; Hemmings, C (Pacini Editore, 2024)
In this paper, we argue that Enggano subordinate clauses beginning with the conjunctions a= and be are morphologically conservative in retaining ergative alignment, whilst other clause types are accusatively aligned. This pattern fits with the typological trend for subordinate clauses to be more conservative than main clauses, but goes against the more widespread pattern of split-ergativity where main clauses have ergative alignment and subordinate clauses have accusative alignment. Consequently, we argue that the Enggano split-alignment pattern is further evidence that historical developments affect different clause types in different ways.